Le malaise des enseignants - Esteve, José M.; Fracchia, Alice F.B. (Revue française de pédagogie, 1988)
Teachers unrest - The authors analyse two types of factors which help the coming out of this unrest and its effects on the personality of teachers and the practice of their profession. Then they propose strategies that could thwart some of these consequences, and plans concerning teachers training and appointment.